Effects of a Cognitive Rehabilitation Programme on the Independence Performing Activities of Daily Living of Persons with Dementia—A Pilot Randomized Controlled Trial - María Jiménez Palomares; María Victoria González López-Arza; Elisa María Garrido Ardila; Trinidad Rodríguez Domínguez; Juan Rodríguez Mansilla (Brain Sciences, 2021)
Background: In all types of dementia, cognitive abilities are affected, behaviour is altered and functional capacity is progressively lost. This cognitive deterioration manifests in the decrease of abilities required to perform the activities of daily living (ADL). The objective of this pilot study was to assess the effect of an Occupational Therapy programme based on the training of ADL through cognitive stimulation on the independence of ADL of persons with dementia. Methods: Institutionalized older adults with major neurocognitive disorder or dementia (N = 58) were randomly allocated to receive either the Occupational Therapy ADL cognitive stimulation programme or conventional Occupational Therapy. The cognitive level and the independence level performing ADL were measured at baseline (week 0), after 5 weeks of treatment (week 5) and after 6 weeks of follow up (week 12). A value of p < 0.05 and α = 0.0025 (Bonferroni correction) was considered as statistically significant. Results: The results obtained showed improvements in the level of independence performing ADLs in the intervention group compared to the control group (p = 0.006). The improvements were seen in relation to feeding (p = 0.001), dressing (p = 0.005) and bladder and bowel incontinence (p = 0.003), the changes observed in feeding are statistically significant. However, those improvements were not maintained after the follow up period. There were no significant changes in relation to the cognitive level (p = 0.741). Conclusions: Occupational Therapy based on ADL cognitive stimulation can have a positive effect, increasing the independence of subjects with major neurocognitive disorder or dementia who are institutionalised.